SMART HOME MENGGUNAKAN INSTRUKSI SUARA - Nova Anggriani Saputri; Puput Dwi Wahyuni; Ocsirendi; Parulian Silalahi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The use of Internet of Things (IoT) technology is currently developing rapidly. One form of application is Smart Home. The existence of this technology affects people's lifestyles to have comfortable and practical housing. This final project aims to develop and test a voice-based Smart Home application using Google Nest Mini. The stages used for this final project are literature study, design, testing, observation and data analysis, using a smartphone and Google Nest Mini 2nd as the main control system, as well as several other additional devices such as nodeMCU ESP8266, relay module, and sinricPRO. Tests were carried out in rooms at different distances with intervals of 0-500 cm. Based on the test results show that at a distance of -300 cm the tool can function properly.